Semaglutide and heart failure: Updated meta-analysis - Barbagelata, Leandro; Masson, Walter; Lobo, Martín; Bluro, Ignacio (Current problems in cardiology, 2024)
Heart failure (HF) is a major contributor to global health challenges, affecting mortality rates and healthcare expenditure. Glucagon-like peptide-1 receptor agonists (GLP-1RA) offer promise in HF management, though their precise impact is unclear. The main objective of this study was to evaluate the effect of semaglutide on HF-related outcomes. We conducted a meta-analysis of studies assessing the effects of semaglutide therapy on HF-related outcomes. This meta-analysis was performed according to PRISMA guidelines. Randomized clinical trials or observational cohorts studies with a follow-up duration ≥ 6 months were included. The random-effects model was performed. Six randomised clinical trials (n = 28,762 patients) and two observational studies were identified and considered eligible for this systematic review. A total of 14,608 subjects were assigned to the semaglutide group and 14,716 individuals were assigned to control or placebo groups. Overall, this meta-analysis shows that semaglutide use was associated with an decreased risk of HF (OR: 0.74; 95 % CI: 0.58 to 0.94, I2 45 %), compared to placebo or control groups. The analytical evaluation does not suggest publication bias, and the sensitivity analysis demonstrated that the result was robust. This meta-analysis demonstrates that the use of semaglutide is associated with a reduction in clinical events related to HF. As HF is a heterogeneous clinical condition, further studies will be necessary to analyze this association in different subgroups of patients.